The Clinical Translation of a Measure of Gain Control: The Contrast-Contrast Effect Task - Barch, Deanna M. (Oxford University Press, 2012)
The goal of the current project was to further develop a measure of gain control—the Contrast-Contrast Effect (CCE)—for use in clinical studies of schizophrenia. The CCE is based on an illusion in which presenting a medium contrast patch surrounded by a high-contrast patch induces individuals to perceive that center patch as having lower contrast than when the patch is presented in isolation. Thus, in the CCE, impaired gain control should lead to more accurate perceptions of the center patch. We tested 132 individuals with Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, schizophrenia or schizoaffective disorder and 130 demographically similar healthy controls. The results indicated that the CCE effect can be obtained with standard equipment, simplified scoring, and a short interstimulus interval (100 ms), revealing a robust suppression of perceived contrast of the center patch when surrounded by a high-contrast annulus. Furthermore, we found a significant reduction in the effect of the high-contrast surround among individuals with schizophrenia, though the effect size was smaller than original reported by Dakin. However, when we eliminated subjects who performed poorly on “catch” trials that controlled for off-task performance, the reduced surround effect among patients was no longer significant in the main analyses. Importantly, this suggests that at least part of the reduced surround effect (if not all) in schizophrenia could be attributable to impaired attentional mechanisms that contribute to off-task performance. Additional analyses suggested that the length of the task could be shortened without losing power to detect surround effects in healthy individuals.